LEGAL SUPPORT FOR THE ASSOCIATION OF UKRAINE WITH THE EUROPEAN UNION - Khomenko, Mykola (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
The aim of this article is to conduct a comprehensive theoretical study of the legal framework for the Association between Ukraine and the European Union. This aim necessitated the following tasks: to define the theoretical and legal foundations of the association between Ukraine and the European Union; describe the main stages of the formation and development of cooperation between Ukraine and the EU as a prerequisite for association; examine the types of association in EU contractual practice; reveal the legal nature and general characteristics of the legal provisions of the Association Agreement between Ukraine and the EU. Research methods: in the course of researching the topic, a historical approach was used to reflect the implementation of international law norms in Ukrainian legislation; a systematic approach was used to clarify the internal essence and nature of the object of research, to study its details and dependence on various factors; logical generalization was used to justify the need to highlight conclusions as a result of the research. Of particular importance in the study was the special scientific method, in particular: the method of interpretation of legal norms used to study the provisions of the Association Agreement between Ukraine and the EU and the content of Ukraine’s national legislation. Results: the article examines the legal basis for Ukraine’s association with the European Union. Analysing the establishment and development of cooperation between Ukraine and the EU in the context of association through the prism of legal grounds and key stages, it is noted that in the early stages, the parties developed relations on a general contractual basis. Political negotiations took place in the format of annual meetings and ongoing consultations between authorised representatives of the parties on the basis of the Partnership and Cooperation Agreement. The initial stage of establishing relations was characterised by low activity in law-making or significant legal changes on the path to Ukraine’s integration into the EU. We attribute this to the EU’s reluctance to expand its borders towards the countries of the former Soviet Union, which were not yet sufficiently democratic, and to the unfavourable performance of the Ukrainian economy. Discussion: the article focuses on the legal nature and general characteristics of the legal provisions of the Association Agreement between Ukraine and the EU.